Design and fabrication of micro-plasma transferred wire arc additive manufacturing system. (May 2022) - Sadasivam, Prakash; Amirthalingam, Murugaiyan
Highlights: This article reports an efforts in developing a micro-plasma transferred wire arc Directed Energy Deposition AM system. The developed system can produce components with a layer thickness from 2 mm and surface roughness of 8-17 μm. This article also describes the system capabilities as a cost effective alternative to laser DED systems. Graphical Abstract: ga1 Abstract: A wire-based Micro-Plasma Transferred Arc Additive Manufacturing (µ-PTAAM) setup is designed and fabricated. This system is developed with an objective to print alloy components with geometries on a laboratory scale under a controlled and safe environment. A Computerized Numerical Control based four-axis system with linear X, Y, Z, and a rotational movement (A) is used to manipulate heat source, wire feeder and the substrate. This system is capable of producing components with dimensions of 200 × 200×150 mm 3 with a weight of up to 50 kg using wire feedstock diameters ranging from 0.2 to 1.4 mm. Due to its low plasma energy and reasonable positioning control, it is possible to deposit thin bead (less than 2 mm) without significantly altering the substrate microstructure. In this paper, the capabilities of the fabricated setup are shown while depositing varying bead geometries using a 0.6 mm ER70S-6 filler wire on a 1.3 mm thick Dual Phase steel (DP 600) and 6 mm thick mild steel substrate. Deposited specimens exhibit defect-free beads with uniform profiles. This study demonstrates that the fabricated micro-plasma AM setup is a competitive alternative to other wire-based directed energy deposition systems.